(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The representation of rare and endangered species of the genus Astragalus L. (Fabaceae) of Ukrainian natural flora in protected territories, collections of botanical garden and dendrological parks was identified and analyzed for partial evaluation of success in implementation of the targets 7 and 8 of the Global Strategy for Plant Conservation in the country until 2020. There aren’t 4 species or 19 % of this group (A. sareptanus A. Beck., A. zingeri Korsh., A. calycinus M. Bieb.) in territories of natural reserved fund of Ukraine. There are 12 species rare and endangered species saved in culture. We allocated 5 species which could be involved in the programs for the restoration and rehabilitation of ecosystems in the short term (A. cicer L., A. cretophilus Klokov., A. glycyphyllos L., A. odessanus Besser, A. ponticus Pall.). There aren’t 3 rare and endangered species (A. exscapus, A. sareptanus, A. calycinus) provided by ex situ and in situ conservation in Ukraine now.